2021
DOI: 10.3390/agriculture11030216
|View full text |Cite
|
Sign up to set email alerts
|

German Farmers’ Attitudes on Adopting Autonomous Field Robots: An Empirical Survey

Abstract: Agricultural production methods in Europe are increasingly subject to public criticism from which many farmers suffer. This applies, among other areas, to the widespread use of pesticides. Autonomous field robots (AFR), as the next stage of agricultural automation, have the potential to farm more intensively and, at the same time, in a more environmentally friendly way. However, a certain skepticism towards autonomous systems is suspected among farmers. Whether farmers adopt a technology depends largely on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
0
14
1
Order By: Relevance
“…Data from the 2018 Latinobarómetro survey reveals that public opinion in Latin America is not generally supportive of robots. This result runs in direct contrast to other studies that find favorable attitudes toward robots in other regions of the world (Rübcke von Veltheim and Heise, 2021, p. 1). Our goal was to identify factors associated with favorable (or less negative) views of robots in the region [22].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Data from the 2018 Latinobarómetro survey reveals that public opinion in Latin America is not generally supportive of robots. This result runs in direct contrast to other studies that find favorable attitudes toward robots in other regions of the world (Rübcke von Veltheim and Heise, 2021, p. 1). Our goal was to identify factors associated with favorable (or less negative) views of robots in the region [22].…”
Section: Discussioncontrasting
confidence: 99%
“…, 2014) and the effect of religion (MacDorman et al ., 2009). More recent studies are focused on attitudes toward robots in agriculture (Rübcke von Veltheim and Heise, 2021) and social services (Carradore, 2021). Also, a recent innovative study by Spatola and Wudarczyk (2021) uses semantic priming to evaluate attitudes toward robots.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(2021) showed that none of the surveyed German farmers had invested in field crop robots, while around 22% had the intention to invest within the coming years. Furthermore, von Veltheim and Heise (2021) concluded that the surveyed German farmers tended to have a neutral to positive view on adopting field crop robots, aligned with von Veltheim et al. (2021), who also found that the surveyed German farmers were positive about introducing autonomous field robots on their farms.…”
Section: Resultsmentioning
confidence: 57%
“…These approaches lack the principles of substantive inclusion identified above (Rose and Bhattacharya, 2023). Examples of participation and inclusion in the technical dimensions of agricultural robotic development have thus far employed a range of tools, including the use of augmented reality (Huuskonen & Oksanen, 2019), on-farm trials (Adamides et al, 2017) and simulation events (see Riek, 2012 for methods), farmer surveys (Rose and Bhattacharya, 2023;Tamirat et al, 2023;von Veltheim and Heise, 2021;von Veltheim et al, 2022), public surveys (Pfeiffer et al, 2021;Spykman et al, 2022) and farmer interviews (Redhead et al, 2015). A recent study in four European countries by Tamirat et al (2023) went further than including only farmers, and instead interviewed robotic companies, academics, project managers, public authorities, and environmental conservation societies.…”
Section: Inclusion For Agricultural Robotics To Datementioning
confidence: 99%